Bibliometric analysis of financial literacy level / Auryn Rahiem, Hasyeilla Abd Mutalib and Norhisam Bulot - Rahiem, Auryn; Abd Mutalib, Hasyeilla; Bulot, Norhisam (Universiti Teknologi MARA, Perlis, 2025)
Financial literacy level refers to the overall understanding of an individual's competency in managing finances. This article presents a bibliometric study on financial literacy. It was conducted using VOSviewer 1.6.18 to assess worldwide research trends, focusing on publication growth, publishing outputs by country, themes of interest, and co-occurrences of author keywords. Bibliometrics is a relatively new research methodology that has grown into a well-established aspect of information research and a quantitative approach to document description. The Scopus database obtained 563 papers published between 2019 and 2023. The literature search statistics indicate a decreasing trend in publishing outputs. Most of the papers came from scholars in the United States, followed by India and China. The keyword "financial literacy" appears most frequently in articles, followed by "financial knowledge." A closer examination of author keyword co-occurrences revealed that "financial literacy" had 242 instances. These findings could guide future research into under-explored aspects of financial literacy.